2012
DOI: 10.1186/1471-2407-12-192
|View full text |Cite
|
Sign up to set email alerts
|

Methylseleninic acid restricts tumor growth in nude mice model of metastatic breast cancer probably via inhibiting angiopoietin-2

Abstract: BackgroundAngiopoietin-2 (Ang-2) plays critical roles in vascular morphogenesis and its upregulation is frequently associated with various tumors. Previous studies showed that certain selenium compounds possess anti-tumor effects. However, the underlining mechanism has not been elucidated in detail. Plus, results of research on the anti-tumor effects of selenium compounds remain controversial.MethodsWe investigated levels of Ang-2 and vascular endothelial growth factor (VEGF) on the estrogen-independent bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In breast cancer, many secretory or cell surface proteins implicated in cell homing to bone, angiogenesis, invasion, and osteoclast recruitment influence the tumor microenvironment in favor of metastasis [ 38 ], so we explore the mechanism of PMS inhibition by detecting angiogenesis. CD31 can be used as a marker of density of microvessel [ 39 ]. As Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, many secretory or cell surface proteins implicated in cell homing to bone, angiogenesis, invasion, and osteoclast recruitment influence the tumor microenvironment in favor of metastasis [ 38 ], so we explore the mechanism of PMS inhibition by detecting angiogenesis. CD31 can be used as a marker of density of microvessel [ 39 ]. As Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of Se in breast cancer prevention and treatment has been studied extensively using in vitro and animal models. It has been reported that Se effectively inhibited cancer cell growth, caused cell cycle arrest, induced apoptosis, reduced angiogenesis and enhanced the efficacy of the anticancer drug, paclitaxel . The majority of current research is focused on deciphering the involvement of Se in early stages of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…All mice were sacrificed at the 15th day after the start of colchicine treatment. The tumor volumes were calculated by the formula: length × width 2 × 0.5 (Wu et al, 2012). The increased tumor volume ratio was calculated as following: tumor volume at day x (Vx) divided by baseline pretreatment tumor volume (V 0 ).…”
Section: Nude Mouse Experimentsmentioning
confidence: 99%